Study on the Design and Load Capacity Calculation Method of Dual-lead Precision Worm Drives - Chen Yonghong; Jin Lianghua; Wang Zhigang; Yuan Hexiang (Jixie chuandong)
In view of the lack of design theory and load-bearing calculation method of dual-lead precision worm drives, the meshing geometry model of the dual-lead worm drive is established based on the principle of spatial meshing, and the design methods of geometric parameters, adjustment and compensation of this worm drive are proposed. Based on the ISO/TS 14521 and using the relative calculation method, loading capacity calculation models for the transmission efficiency, tooth surface wear, tooth surface pitting and tooth root broken are developed. The dual-lead precision worm drive prototype is designed and manufactured, and the transmission performance test is carried out. Through the theoretical analysis, simulation calculation and prototype performance experiment, the correctness of the design method and the reliability of the load-bearing calculation method are verified, which provides a theoretical basis for the design and analysis of the wide application of dual-lead precision worm drives.